The role of emotional dependence in the relationship between attachment and impulsive behavior - Estévez, Ana; Chávez-Vera, María D.; Momeñe, Janire; Olave, Leticia; Vázquez, Daniel; Iruarrizaga, Itziar (Anales de Psicología / Annals of Psychology, 2018)
The emotional dependence has been related with the problems in the impulse control and with the preoccupied attachment style. The objectives of this study are to analyze the relation between the emotional dependence, attachment and the impulsive behavior, as well as, to analyze if these final two can predict the emotional dependence. Furthermore, it analyze if the emotional dependence mediate in the relation between attachment and impulsivity and, finally, it studies the differences of gender in the three mentioned variables. The sample is formed by 1533 teenagers (707 women and 826 men), with ages between 14-18 years old (M = 15.76; DT = 1.25). The results showed of positives relations between the emotional dependence and the parental permission, childhood trauma and impulsive behavior. Moreover, the impulsivity is positively related with the fact to avoid to be alone, asymmetric relation, the need to please others, parental permission and childhood trauma. In the same way, it proves how the parental permission, self-sufficiency and resentment against parents and childhood trauma can predict the emotional dependence. Finally, it observes how the relation between the attachment and the impulsive behavior is mediated with the emotional dependency and it appreciates differences between the three variables in gender basis.